2020
DOI: 10.31332/lifalah.v5i2.2253
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Waqf to Alleviate Poverty Among Muslims in Oyo State South-West, Nigeria: Test of Theory of Planned Behaviour

Abstract: Poverty is on the increase in Africa in general and specifically in Nigeria despite the numerous poverty alleviation programs of successive governments. Lamentably, most poverty alleviation initiatives have failed to produce meaningful outcomes despite billions of Naira committed to them. Nigerians and Nigeria still ranked among the poorest, with the poverty rate rising since the 1980s. Base on the theory of planned behavior, this study examines the influences of attitude, subjective norm, perceived behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
1
12
1
Order By: Relevance
“…From the findings of the first hypothesis, the current study indicated that attitude has no significant effect on the establishment of waqf institutions for poverty alleviation. However, the result of this study contradicts the finding of the study conducted by Abdulkareem et al (2020), which found that attitude has significant influenced the establishment of waqf for poverty alleviation. The cause of the different results may come because of the differences in the environment, population, and the classification of the study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…From the findings of the first hypothesis, the current study indicated that attitude has no significant effect on the establishment of waqf institutions for poverty alleviation. However, the result of this study contradicts the finding of the study conducted by Abdulkareem et al (2020), which found that attitude has significant influenced the establishment of waqf for poverty alleviation. The cause of the different results may come because of the differences in the environment, population, and the classification of the study.…”
Section: Discussioncontrasting
confidence: 99%
“…Iman et al, (2021) argued that the better the attitude toward waqf behavior, the better the participation in waqf. Similarly, Abdulkareem et al, (2020) noted that an individual is more likely to contribute to the establishment of waqf institutions if they have a positive attitude toward doing so. In the context of this study, the greater the person's intention toward establishing waqf institutions, the more likely it is that the person will participate in the waqf establishment.…”
Section: Attitudementioning
confidence: 99%
“…Alifiandy et al (2020) examined the relevance of TPB model in understanding the donor's intention (waqif) to contribute in Airlanga, Indonesia. Abdulkareem et al (2020) surveyed 218 Islamic scholars in Oyo State, Nigeria, and ATT, SN, PBC, and religiosity increased donor's intention to establish waqf.…”
Section: Tpb and Intention To Donate To Waqfmentioning
confidence: 99%
“…Detail information is important in order to accept new things or products such as Sukuk. This is because the availability of information can assist with upgrade comprehension of the usefulness of Sukuk among investors (AbdulKareem, 2017., AbdulKareem et al, 2020d. Pikkarainen et al, (2004) contended that the amount of information that is accessible to the behaviour of a specific system.…”
Section: Amount Of Informationmentioning
confidence: 99%